2020
DOI: 10.1002/ehf2.12860
|View full text |Cite
|
Sign up to set email alerts
|

Cushing syndrome cardiomyopathy: an unusual manifestation of small‐cell lung cancer

Abstract: Cushing syndrome is a rare cause of dilated cardiomyopathy and heart failure with reduced ejection fraction. Cases describing this association are scarce. We describe a patient presenting with acute heart failure, new cardiomyopathy, refractory hypokalaemia, severe hyperglycaemia, and uncontrolled hypertension who was found to have hypercortisolism secondary to an ectopic adrenocorticotropic hormone-secreting primary lung neoplasm. This case highlights the effects of hypercortisolism on the myocardium. The fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The mortality in CS is increased significantly with a standard mortality rate (SMR) of 3.68 (2.34-5.33) (1). A study of adrenal incidentaloma with a mean follow-up of 7.5 years showed that, compared with patients with non-secretory adrenal incidentaloma, patients with subclinical hypercortisolism had a nearly four-fold increase in all-cause mortality (8.8 vs. 43%), a 10% higher incidence of cardiovascular events (6.7 vs. 16.7%) and a 7.6 times higher incidence of cardiovascular mortality (2.5 vs. 21.6%) (2). In addition, compared with the patients with a cortisol level <1.8 µg/dL after the dexamethasone suppression test, the patients with a cortisol level between 1.85 and 5 µg/dL had a higher mortality hazard ratio of 12.0 (1.6-92.6), and patients with a cortisol level >5 µg/dL had the highest mortality hazard ratio of 22.0 (2.6-188.3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality in CS is increased significantly with a standard mortality rate (SMR) of 3.68 (2.34-5.33) (1). A study of adrenal incidentaloma with a mean follow-up of 7.5 years showed that, compared with patients with non-secretory adrenal incidentaloma, patients with subclinical hypercortisolism had a nearly four-fold increase in all-cause mortality (8.8 vs. 43%), a 10% higher incidence of cardiovascular events (6.7 vs. 16.7%) and a 7.6 times higher incidence of cardiovascular mortality (2.5 vs. 21.6%) (2). In addition, compared with the patients with a cortisol level <1.8 µg/dL after the dexamethasone suppression test, the patients with a cortisol level between 1.85 and 5 µg/dL had a higher mortality hazard ratio of 12.0 (1.6-92.6), and patients with a cortisol level >5 µg/dL had the highest mortality hazard ratio of 22.0 (2.6-188.3).…”
Section: Introductionmentioning
confidence: 99%
“…Since CS is a rare disease with an incidence of 2-5/10 6 /year, CS complicated with cardiomyopathy is rarely seen among the known causes. A search of the literature found that there were only a few case reports about CS complicated with cardiomyopathies, in which the major type was DCM (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). If CS induces cardiomyopathies, it is speculated that the mortality risk of CS patients will be further aggravated.…”
Section: Introductionmentioning
confidence: 99%